Systematic evaluation of graphene quantum dot toxicity to male mouse sexual behaviors, reproductive and offspring health. (February 2019) - Zhang, Ding; Zhang, Zefei; Wu, Ying; Fu, Kai; Chen, Yang; Li, Wenhao; Chu, Maoquan
Abstract: Graphene quantum dots (GQDs) have attracted considerable attention across multiple fields, particularly biomedical research. However, the effects of GQDs on reproductive and offspring health in mammals are unclear. Here, we show that GQD exposure via oral gavage or intravenous injection had no effect on the frequency and timing of sexual behaviors in male mice. GQD-exposed male mice retained healthy structural and functional reproductive physiology (e.g., production and storage of healthy sperm, maintenance of normal total protein and key enzyme concentrations in testes) of the testes and epididymides, as well as normal testosterone levels. Female mice housed with GQD-exposed males produced first, second, and subsequent litters of healthy pups without obvious differences to females housed with buffer-treated males. These findings may be explained by the low toxicity of GQDs in germ cells and their rapid excretion after exposure in mice, mainly via the urine and/or feces; GQDs, even at high doses, are virtually undetectable in male mouse testis, epididymis, and brain. Our findings reveal the short- and long-term effects of GQD exposure on male mouse sexual behaviors, reproductive activity, and offspring development and indicate the potential mechanisms of action of GQDs to provide further insight into their bio-safety.